2006
DOI: 10.1158/1078-0432.ccr-06-0384
|View full text |Cite
|
Sign up to set email alerts
|

In vitroPeptide Immunization of Target Tax Protein Human T-Cell Leukemia Virus Type 1–Specific CD4+ Helper T Lymphocytes

Abstract: Purpose: Adult T-cell leukemia/lymphoma induced by human T-cell leukemia virus type 1 (HTLV-1) is usually a fatal lymphoproliferative malignant disease. HTLV-1 Tax protein plays a critical role in HTLV-1-associated leukemogenesis and is an attractive target for vaccine development. Although HTLV-1Tax is the most dominant antigen for HTLV-1-specific CD8 + CTLs in HTLV-1-infected individuals, few epitopes recognized by CD4 + helper T lymphocytes in HTLV-1Tax protein have been described. The aim of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…Here, we show for the first time that the LMP1 antigen is processed and presented to CD4 HTLs in the context of HLA class II molecules through the endogenous (direct presentation by transformed cells) or the exogenous (antigens captured and processed by conventional APC) pathways. In our studies, three peptides (LMP1 [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] , LMP1 102-116 , and LMP1 159-175 ), which did not correspond to those described by Leen and Depil (24,25) were predicted to potentially function as promiscuous HTL epitopes. Out of the three peptides, only one, LMP1 159-175 , proved to be effective at inducing HTL responses.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Here, we show for the first time that the LMP1 antigen is processed and presented to CD4 HTLs in the context of HLA class II molecules through the endogenous (direct presentation by transformed cells) or the exogenous (antigens captured and processed by conventional APC) pathways. In our studies, three peptides (LMP1 [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] , LMP1 102-116 , and LMP1 159-175 ), which did not correspond to those described by Leen and Depil (24,25) were predicted to potentially function as promiscuous HTL epitopes. Out of the three peptides, only one, LMP1 159-175 , proved to be effective at inducing HTL responses.…”
Section: Discussionmentioning
confidence: 59%
“…As with previous studies (22,(30)(31)(32)(33)(34)(35)(36), an MHC class II peptide binding predictive algorithm (29) was used to select candidate peptides from the LMP1 sequence that would bind to the products of three common human MHC class II alleles (HLA-DR1, HLA-DR4, and HLA-DR7). Three peptides, LMP1 [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] (ALLFWLYIVMSDWTG), LMP1 102-116 (GQALFLGIVLFIFGC), and LMP1 159-175 (YLQQNWWT-LLVDLLWLL) were identified as potentially binding the three MHC class II alleles (data not presented), suggesting these could function as promiscuous HTL epitopes. In past studies, we have observed that peptide sequences predicted to bind to HLA-DR1, HLA-DR4, and HLA-DR7 have elicited HTL responses restricted by additional MHC class II alleles, such as DR9, DR13, DR15, or DR53 (22,30,32,(34)(35)(36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14). The in silico prediction system that was used is based on the algorithm tables described by Southwood et al (14) and has been useful in identifying HTL epitopes from numerous TAAs (15,(17)(18)(19)(20)(21)(22)(23)(24)(25). In many instances, the predicted peptides were able to elicit HTL responses restricted by MHC class II alleles other than HLA-DR1, HLA-DR4, and HLA-DR7 (e.g., HLA-DR9, HLA-DR13, HLA-DR15, HLA-DR51, HLA-DR52, and HLA-DR53), indicating that this prediction system extends beyond the original three MHC alleles.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are only a few reports of HTLV-1-specific Th cell responses (20)(21)(22)(23), presumably because of their susceptibility to HTLV-1 infection in vivo and in vitro (24). Preferential HTLV-1 infection in HTLV-1-specific CD4 + T cells could be one of the reasons for immune suppression in ATL patients.…”
mentioning
confidence: 99%